Students’ Errors in Using Punctuation and Capitalization - Ayu Oktaviani; Dewi Syafitri; Sastika Seli (EDULIA: English Education, Linguistic and Art Journal, 2022)
The aims of this research are to know what are the errors made by the tenth grade students at MAN 2 lubuklingau in using punctuation marks in writing descriptive text and to know the dominant errors made by the tenth grade students at MAN 2 Lubuklinggau in using punctuation marks in writing descriptive text. The sample of the research was tenth grade students at MAN2 Lubuklinggau. the writer used simple quantification. This is because this study did not measure the students’ achievement in writing, but merely to find out the grammatical errors in students’ writing. It tries to find out the types of error produced by the students in their writing, as well as the most type of errors made by the students. The main instrument that the writer used in this study was writing test. The type of errors made by the tenth grade students at MAN2 Lubuklinggau in using punctuation marks in writing descriptive text are divided into three types that had been analyzed. The first highest frequency of error made by the tenth grade students at MAN2 Lubuklinggau in using punctuation marks in writing descriptive is omission. Key words: Error, Punctuation, Capitalization